Timing and Format of New Synchronous Online Assessment: IIUM Experience with Preclinical Medical Students - Mohd Radzuan, Hazulin; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Abdul Rahim, Roslina; Khaing, Aye Thi; Ismail, Soraya; Ismawi, Hidayatul Radziah; Mat Harun, Noraihan; Mohamed Bakrim, Norbaiyah; Abd. Rahim, Nour El Huda; Mohd Noor, Mohd Fadly; Wan Omar, Wan Fatein Nabeila; et al. (2021)
This poster was submitted to the International Putra Innovative Teaching and Learning (PicTL) 2020 poster competition that was held in University Putra Malaysia from 22-30 October 2020. It represented the outcome of the new assessment format and timing of the synchronous online quiz that was carried out during the emergency remote teaching and learning period among IIUM preclinical medical students. This poster won a Bronze Medal Award.